Evaluación de la aplicación de varias dosis de ácido monosilisico en la producción del cultivo de arroz. var. iniap 15 - Orejuela, Juan (2010)
The project was conducted in the Rinconada enclosure of the Daule city, Guayas province. The investigation had as main objective the evaluation of the effect it has on the rice plant (variety INIAP 15), applying ZUMSIL (monosilísico acid) in various doses (0cc/Ha, 100cc / Ha, 200c / Ha, 300cc / Ha , 400cc / 500cc Ha and / Ha). To achieve this objective established a study area, which was subdivided into plots of sampling measures 2 x 2m, applications in the sample plots were made after transplantation on days 15, 30 and 45. We proceeded to choose 16 points randomly to experimental which the measurements were performed. The variables studied were: plant height, number of tillers, days to flowering, average grain weight per spike and average production.Was performed foliar application of the product, data on plant height and number of tillers were taken every 15 days from 15 to 45 days after transplantation, days taken to flowering, was performed by counting grains Tang, was harvested and weighed the production of the experimental units. The best treatments were 200 ml / ha followed by 100cc/Ha. It was concluded that these were the best dose and recommended for application to rice variety